Enhanced energy-storage properties in lead-free (Bi0.5Na0.5)TiO3-based dielectric ceramics via glass additive and viscous polymer rolling process. Issue 11 (1st June 2022) - Zhang, Leiyang; Sun, Hongchen; Lan, Yu; Tang, Mingyang; Li, Yang; Alikin, D.O.; Shur, V. Ya; Gao, Jinghui; Lu, Xu; Wei, Xiaoyong; Xu, Zhuo; Jin, Li
Abstract: Dielectric materials with a high recoverable energy-storage density ( W rec ) and an enhanced power density are required for downsizing pulsed power electronic devices. Dielectrics with a low but temperature-stable permittivity are better suited as energy-storage materials for power devices owing to their delayed saturation polarization response. ABO3 perovskite-structured (Bi0 . 5 Na0.5 )TiO3 -based [(Bi0 . 5 Na0.5 )0.93 Ca0.07 ](Ti0 . 85 Zr0.15 )O3 (BCZ) lead-free ceramics exhibit good dielectric temperature stability and are being investigated as viable materials for energy-storage devices. However, these materials only produced limited W rec due to the reduced breakdown strength (BDS). Herein, various advanced engineering techniques, including glass doping and the viscous polymer rolling process, were applied to the BCZ to substantially enhance the BDS of the ceramics. Our results show that the BCZ-0.75 wt% glass-additive composition achieved an ultrahigh W rec of 7.78 J/cm 3 under a comparatively low electric field and remained above 4.6 J/cm 3 in the temperature range of 30 °C–160 °C. This work demonstrates that the BCZ is a viable competitor for lead-free dielectrics and guides for the development of novel high-performance dielectric materials for future pulsed power devices.